Types and Factors of Code-Switching in Deddy Corbuzier’s Podcast - Yulia Mutmainnah (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
With the increasingly sophisticated technology, especially in the field of communication, and the ease with which people can mobilize from one area to another, the phenomenon of code-switching has become a very common thing, including the conversation between Deddy Corbuzier and Agnez Monica in a Deddy Corbuzier’s podcast on the YouTube channel entitled "Agnez Mo.. Mantan Ku Ter...". This study aims to analyze the types of code-switching contained in the podcast and the factors that influence it based on Hoffman's (2019) theory. The research method of this study is the qualitative descriptive method. The results of this study indicate that all types of code-switching are present in the conversation between Deddy Corbuzier and Agnez Monica. However, there are only five factors that influence the occurrence of code-switching to appear in the conversation.